Hypothetische Kausalität und Kontrafakten Eine interdisziplinäre Analyse zur Beachtlichkeit von Reserveursachen im zivilen Schadensrecht - Kaufhold, Maria (Studien zum Zivilrecht, 2022)
The author deals with the topic of preemtion in tort law. After addressing the question of whether the conditio-sine-qua-non theory (but-for-rule) is a suitable theory to detect causation in tort law, she turns to the counterfactual theory of causation of the philosopher David Lewis and to "counterfactuals", which are used to examine hypothetical causal processes in history and political science. With the help of this interdisciplinary approach, the author ultimately argues that hypothetical causes should be taken into account in tort law